Effect of Conservation Agriculture on Aphid Biocontrol by Generalist (Carabid Beetle) and Specialist (Parasitoids Wasp) Natural Enemy Communities in Winter Wheat - Sacco–Martret de Préville, Ambre; Ortiz-Martinez, Sebastian; Plantegenest, Manuel; Canard, Elsa (Frontiers in Ecology and Evolution, 2022)
Adoption of practices that reduce the risk of pest outbreaks is one of the pillars of agroecology and is largely based on biological control. Multiple infield and landscape parameters affect biocontrol, but the effects of conservation soil management on biological control have been poorly investigated over crop season. By comparing couple of winter wheat fields with the same landscape, the direct and indirect effects of soil management (conservation and conventional systems) on natural enemies’ communities and their biological control on aphids was studied from the tillering stage to the harvest. In addition to aphid infestation, two families of the main natural enemies’ guilds were monitored, as well as their associated services: aphid parasitoid, a specialist and flying natural enemy, with parasitism service, and carabid beetles, a generalist and ground-dwelling predator, with aphidophagy service. Soil conservation system hosted more abundant and diverse carabid beetles’ assemblages, and received higher aphidophagy service in June than conventional system. However, neither parasitoid abundance, nor parasitism rates, were affected by soil management. Aphid infestation and its associated damage did not depend on soil management either. Our results suggest that ground-dwelling natural enemies are, more impacted by soil management than foliage-dwelling natural enemies, which is partially reflected in aphid biocontrol. Agricultural systems with reduced soil perturbation may result in lower direct mortality on ground-dwelling communities due to tillage than in a conventional system but also in higher habitat heterogeneity, increasing the number of ecological niches for natural enemies. Both factors are supposed to favor an early presence of natural enemies and a trend of a precocious aphidophagy service is indeed observed in conservation system.